Social representations, human capital and knowledge production in the Covid-19 era - Cruz García Lirios (Malikussaleh Journal of Mathematics Learning (MJML), 2021)
Studies of propaganda, security, warn youth and old age; 1) the systematic dissemination of crimes Attributed to political corruption; 2) state advertising as legitimate security administrator His rectory; 3) the de-legitimation of Citizens to Consider them incapable of preventative crime Initiatives; 4) are excluded by the industries older Assuming That They are incapable of self-monitoring and self-care. Specify a model for studying the effects of advertising social security in the representations of aging, youth and old age. A non-experimental, retrospective and exploratory study with a nonrandom was Conducted selection of indexed sources the discretion of explanatory variables Between correlations paths... The model included three hypotheses to Explain the paths of correlations Between four and seven indicators constructs for each. The revised theoretical, conceptual and empirical frameworks warn the inclusion of other variables such as helplessness, self-control farsightedness, beliefs, attitudes and intentions That would complement the specified model. A comprehensive model would Explain the correlations paths from theoretical frameworks That Establish the Difference between crime prevention capabilities, systematic observation of corruption with emphasis on Impunity.